2021
DOI: 10.1097/aud.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Cortical Auditory Evoked Potential in Cochlear Implant Users

Abstract: Objectives:The primary goal of the study was to investigate electrical cortical auditory evoked potentials (eCAEPs) at maximum comfortable level (MCL) and 50% MCL on three cochlear implant (CI) electrodes and compare them with the acoustic CAEP (aCAEPs), in terms of the amplitude and latency of the P1-N1-P2 complex. This was achieved by comparing the eCAEP obtained with the method described and stimulating single electrodes, via the fitting software spanning the cochlear array and the aCAEP obtained using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…It is also possible that CAEPs are affected by the bandwidth and duration of the stimulus. According to the HEARLab manual, /s/ has the stimulus duration of 50ms, /g/ 20 ms, /t/ 30 ms, and /m/ 30 ms. As reported by Tavora-Vieira et al ( 2021), the artifact of the HEARLab recordings starts from 0 ms onwards, and it is larger for the speech token /s/, probably due to the longer stimulus duration [43]. Nevertheless, clinicians might consider working with these CI users to gradually improve their acceptance to high frequencies sounds to see if a CAEP response can be elicited.…”
Section: Plos Onementioning
confidence: 73%
“…It is also possible that CAEPs are affected by the bandwidth and duration of the stimulus. According to the HEARLab manual, /s/ has the stimulus duration of 50ms, /g/ 20 ms, /t/ 30 ms, and /m/ 30 ms. As reported by Tavora-Vieira et al ( 2021), the artifact of the HEARLab recordings starts from 0 ms onwards, and it is larger for the speech token /s/, probably due to the longer stimulus duration [43]. Nevertheless, clinicians might consider working with these CI users to gradually improve their acceptance to high frequencies sounds to see if a CAEP response can be elicited.…”
Section: Plos Onementioning
confidence: 73%
“…Távora-Vieira et al (31) demonstrated that in experienced CI users with SSD, aided aCAEPs could be recorded successfully when the contralateral ear was masked. The results indicated that aCAEPs could potentially be used as a clinical tool to facilitate verification of MCLs in adults.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to determine whether different response patterns are due to neurophysiologic processing or the speech processor. Using direct electrical stimulus instead of acoustic stimulus eliminates these differences (12,13). Current studies have shown that eALR latency and amplitudes have good test-retest reliability in moderate to short-term (14,15).…”
mentioning
confidence: 95%